Effect of biostimulants on the growth of “skeleton cut” pruning coffee trees (Research, Society and Development, 2022)
The brazilian coffee growing has been highlighted on mundial scenario, because of the application of appropriate and efficients managements that provides high productivities. Among these managements, the use of prunings, that aim the renewal of the aerial part of the plant. The using of biostimulants after the pruning can provide better conditions to the growth and the renovation of the aerial part. Thereby, the objective was to appraise the effect of the biostimulants application, after the pruning, in the growing of coffee bushes. The experiment was conducted in São Manoel farm located in the Muzambinho city. The statistic plan used was randomized block design (DBC) in a factorial scheme 3 x 2 + 1, being three fraction types of the recommended dose (1, 2 and 3 fractions) and two application ways (by leaf and by soil) and an control treatment, totalizing 7 treatments with 4 replications and 28 experimental units. Each experimental unit was composed by 3 coffee lines with 10 plants by line, being considered an useful fraction only the central line and the 4 central plants. The biostimulant application provided, in a general way, gains in numbers of leafs in plagiotropic branches of coffee plants. The biostimulant didn't interfere with plants height, but the positives effects was watched mostly in the first months after the application, when the difference between the treatments was more accentuated. The application of biostimulants don't need fractions, it can be use in an only fraction, being an efficient technique aiming at the growth increment.